Diving patterns of female macaroni penguins breeding on Marion Island, South Africa - (:unkn) unknown (My University, 2011)
Despite the large biomass of macaroni penguins Eudyptes chrysolophus in the Southern Ocean, their feeding ecology is poorly known at some important breeding localities. We investigated the diving behaviour and diet of female macaroni penguins feeding small chicks on Marion Island (468520S, 37850E), South Africa, one of the species' most northerly breeding sites, supporting 4% of their global population. We then compared our results with similar studies from other localities. In December 2008, we collected information on 12 foraging trips from 6 individuals using time-depth recorders, as well as diet from 42 individuals. Median trip duration was 22.8 h (5.6-80.8 h). Penguins performed 42.8 ± 15.9 dives per hour at sea, with dive depths averaging 24.6 ± 8.6 m and lasting 40.8 ± 12.1 s, although 74.3% of dives were \10 m. Euphasids dominated their diet (86% by mass), mainly Thysanoessa vicina. A second peak in dive depths at 55-80 m might reflect the 12% of fish in their diet. The substantial proportion of shallow night dives (30% of total dives) suggests some foraging occurs at night. Differences in diving patterns of individual macaroni penguins in this study confirmed the behavioural flexibility of these birds reported from other breeding localities. However, most other studies assumed that dives\3-5 m were commuting dives whereas our study suggests that at least some prey are caught during shallow dives. We highlight how different analytical methods can change the outcome of studies. Despite macaroni penguins' apparent flexibility in foraging behaviour during the breeding season, their numbers are decreasing globally. Further investigations of their foraging behaviour are needed to assess potential competition with other predators and krill fisheries.
Keywords: African Research